The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/pros.20741
|View full text |Cite
|
Sign up to set email alerts
|

Potent Oncolytic activity of human enteroviruses against human prostate cancer

Abstract: Enteroviruses CVA21, CVA21-DAFv, and EV1 are potentially potent oncolytic agents against human prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…9,10,1618 Another factor of probable relevance was the high dose of virus administered. Dose-response relationships for antitumor efficacy and virus delivery have been well documented in previous virotherapy studies, 7,15,19,20 and a dose-threshold effect can be mathematically predicted. 20 Also, measles virus transcripts were still detectable in the circulating cells of patient 1 at 6 weeks after virus infusion, by which time there had been a substantial boost to her antimeasles antibody titer, suggesting the possibility of continuing ongoing oncolytic activity even at that late time.…”
Section: Discussionmentioning
confidence: 88%
“…9,10,1618 Another factor of probable relevance was the high dose of virus administered. Dose-response relationships for antitumor efficacy and virus delivery have been well documented in previous virotherapy studies, 7,15,19,20 and a dose-threshold effect can be mathematically predicted. 20 Also, measles virus transcripts were still detectable in the circulating cells of patient 1 at 6 weeks after virus infusion, by which time there had been a substantial boost to her antimeasles antibody titer, suggesting the possibility of continuing ongoing oncolytic activity even at that late time.…”
Section: Discussionmentioning
confidence: 88%
“…Systemic administration would be preferable in targeting advanced disease but has usually shown clearly limited efficacy (Berry et al , 2008; Li et al , 2013). Furthermore, preclinical oncolytic virotherapy research in prostate cancer has relied heavily on subcutaneous tumour models due to the high technical demands of orthotopic inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that CVA21 is able to rapidly target and lyze a variety of cancer cell types [10][11][12][13][14] expressing high levels of the CVA21 cellular receptors, ICAM-1 and DAF. Herein, the cell surface expression of these receptors was examined in a panel of normal and cancerous breast, colorectal, and pancreatic cell lines.…”
Section: Expression Of Icam-1 and Daf On Cancer Cell Linesmentioning
confidence: 99%
“…One oncolytic virus that is currently under investigation is the wild-type genetically unmodified human enterovirus, Coxsackievirus A21 (CVA21), which induces mild upper respiratory symptoms during natural infection of humans [7][8][9]. Recently, we have shown that CVA21 is an efficient oncolytic agent that specifically targets and rapidly lyzes human malignant melanoma, multiple myeloma, prostate and breast tumors [10][11][12][13][14] expressing upregulated levels of the CVA21 cellular receptors both in vitro and in vivo. In addition, a Phase I clinical trial in late stage melanoma patients has recently been completed, and has demonstrated that intratumorally administered CVA21 (tradename CAVATAK™) is well tolerated in humans, and that 55.55% of patients experienced stabilization or reduction in injected tumor volumes (Smithers and Shafren, unpublished data).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation